General concept of wound healing, revisited (Medical Journal of Indonesia, 2009)
Wound healing is a transition of processes which is also recognized as one of the most complex processes in human physiology. Complex series of reactions and interactions among cells and mediators take place in the healing process of wound involving cellular and molecular events. The inflammatory phase is naturally intended to remove devitalized tissue and prevent invasive infection. The proliferative phase is characterized by the formation of granulation tissue within the wound bed, composed of new capillary network, fibroblast, and macrophages in a loose arrangement of supporting structure. This second phase lasts from day 8 to 21 after the injury is also the phase for epithelialisation. The natural period of proliferative phase is a reflection for us in treating wound to reach the goal which ultimately defines as closed wound. The final maturation phase is also characterized by the balancing between deposition of collagen and its degradation. There are at least three prerequisites which are ideal local conditions for the nature of wound to go on a normal process of healing i.e. 1) all tissue involved in the wound and surrounding should be vital, 2) no foreign bodies in the wound, and 3) free from excessive contamination/infection. The author formulated a step ladder of thinking in regards of healing intentions covering all acute and chronic wounds. Regarding the “hierarchy” of healing intention, the first and ideal choice to heal wounds is by primary intention followed by tertiary intention and lastly the secondary intention. (Med J Indones 2009;18:206-14)